Increased Human Leukocyte Antigen-G Expression At The Maternal-Fetal Interface Is Associated With Preterm Birth - STOUT, Molly J. (J Matern Fetal Neonatal Med, 2014)
OBJECTIVE: The maternal-fetal interface must modulate immune function to allow tolerance of fetal cells while still reacting to pathogens to suppress infection. Human leukocyte antigen-G (HLA-G) is a class Ib major histocompatibility complex protein involved in maternal-fetal tolerance. We posited that alterations in placental HLA-G expression predispose women to preterm birth. The aim of this study was to compare HLA-G expression in the maternal-fetal interface of term versus preterm human placentas. METHODS: We performed a cross-sectional study of specimens from the basal plate of the human placenta from women enrolled in a tissue specimen and clinical data consortium. Immunohistochemistry with digital microscopic analysis was used to quantify HLA-G protein expression in the basal plate from preterm and term placentas. RESULTS: Preterm birth <37 weeks occurred in 29.5% of 149 singleton pregnancies. HLA-G-positive cells occupied one-third of the basal plates, and the HLA-G-positive area was increased by 14% in placentas from preterm births than in those from term births (32.1% in term placentas versus 36.6% in preterm placentas). CONCLUSION: Although HLA-G is required for maternal tolerance of the semi-allogeneic fetus, higher levels of HLA-G expression at the maternal fetal interface is associated with preterm birth.